1, 2‐Thiazines: One‐Pot Syntheses Utilizing Mono and Diaza Analogs of Sulfones. Issue 20 (5th April 2016) - Bohmann, Rebekka Anna; Unoh, Yuto; Miura, Masahiro; Bolm, Carsten
Abstract: A one‐pot Michael addition/cyclization/condensation reaction sequence for the regioselective synthesis of 1, 2‐thiazines, starting from propargyl ketones and N H‐sulfoximines or N H‐sulfondiimines, has been developed. Under mild and operationally simple reaction conditions previously unprecedented 1, 2‐thiazine 1‐imide and 1‐oxide derivatives are formed in good to excellent yields. The products represent heterocyclic building blocks, readily modifiable by a regioselective C−H bond functionalization, classical cross‐coupling reactions, and deprotection. Abstract : All in one ! One‐pot Michael addition/cyclization/dehydration sequences provide access toward 1, 2‐thiazine derivatives (see scheme). In this manner, mono and diaza analogs of sulfones are assembled in 3D heterocyclic motifs.